Towards ‘Another of Me’: Random Para Tolol :v and The Language Games - Satria, Faudyan Eka (Journal of Islamic World and Politics, 2019)
When social media experiences an escalation in the number of users until today, now social media offers an alternative for the community in constructing more intimate social relations. This is likened to a new world that Tom Boelstorff has tried to discuss in Second Life. Absolutely, here, the identity will find its intersection: could it reproduce? In some cases, that question turns the answer: "yes". For example in a Facebook group called Random The Tolol: v (RPT: v). Not just building an image as a community  that shares jokes as shown on its group?s timeline, there is a tendency to "become Spanish" when its members almost use Spanish phrases in each of their post captions frequently. What is interesting is that RPT: v is an Indonesian community. At the same time, to be honest, this language politics case also involved me who had long joined the RPT :v. Therefore, by using the method of digital ethnography research that has an autoetnographical character, I will try to explore more deeply what the meaning of language for members of RPT :v which simultaneously can (re)form their identity in the internet?